Community Participation Analysis in Community Based Tourism Development (PBM) in Pentingsari Tourism Village - Khairune Nisa, An Nuur (Jurnal Toursci, 2023)
This study aims to identify the geographical area of Pentingsari Village as a village that offers experiential tourism activities in the form of learning and interaction about nature, the environment, agriculture, plantations, entrepreneurship, socio-cultural life, various traditional arts, and local wisdom still profoundly rooted in the community with a typical rural atmosphere on the slopes of Mount Merapi. The study used qualitative data with two data sources, namely primary and secondary. Primary data comes from interviews and observations, while secondary data comes from various sources such as the web, journals, electronic media, social media, and other mass media. Data analysis techniques in this study use qualitative descriptive data analysis techniques. The results and conclusions show that the economic principles in Pentingsari Village have been fulfilled because the community already has local products that are proven to increase community income, have been managed by the residents themselves, and have been independent. The political principle has been fulfilled because the community has actively managed the tourism village, is responsive to the community's needs, and works together to overcome it. The level of power of the residents has fully managed the tourism village democratically.